Effect of dissolved organic matter on the bioavailability and toxicity of cadmium in zebrafish larvae: Determination based on toxicokinetic–toxicodynamic processes. (1st November 2022) - Gao, Yongfei; Zhu, Jingxue; He, An
Highlights: The organic acid binding Cd 2+ activities were up to the concentrations of acid. The BL–TK–TD model simulated the protective effect of fulvic acid. The BL–TK–TD model overestimated the complexing capacity of citric acid. The BL–TK–TD model simulated the protective effects of native DOM in most cases. The observed LC50 s of Cd showed a peak effect for the hydrophilic acidic contents. Abstract: The presence of dissolved organic matter (DOM) strongly influences the bioavailability of metals in aquatic environments; however, the association between the binding activities and the concentrations of DOM compositions is not well documented, leading to uncertainties in metal toxicity assessment. We creatively quantify the mitigation and acceleration effects of DOM compositions on cadmium (Cd) bioaccumulation and toxicity in zebrafish larvae using abiotic ligand (ABLs) and biotic ligand (BLs) in a toxicokinetic–toxicodynamic (TK–TD) model. The BL–TK–TD model could accurately predict the protective effect of fulvic acid while overestimating the complexing capacity of citric acid. The model also could successfully simulate the protective effects of native DOM in most cases from 32 natural water bodies in China. The observed LC50 values of Cd showed a peak effect for the native DOM fraction comprising hydrophilic acidic contents (3.55 ± 0.44 mg L − 1 ) in natural water from 32 sites. The BL–TK–TD model provides practically useful information to identify the effect of different DOM compositions on metal bioavailability and toxicity in aquatic environments and guides future water management policies aimed at controlling aquatic heavy metal pollution. Graphical abstract: Image, graphical abstract